Neonatal Acute Kidney Injury - Selewski, David T; Charlton, Jennifer R; Jetton, Jennifer G; Guillet, Ronnie; Mhanna, Maroun J; Askenazi, David J; Kent, Alison L (Pediatrics (Evanston), 2015)
In recent years, there have been significant advancements in our understanding of acute kidney injury (AKI) and its impact on outcomes across medicine. Research based on single-center cohorts suggests that neonatal AKI is very common and associated with poor outcomes. In this state-of-the-art review on neonatal AKI, we highlight the unique aspects of neonatal renal physiology, definition, risk factors, epidemiology, outcomes, evaluation, and management of AKI in neonates. The changes in renal function with gestational and chronologic age are described. We put forth and describe the neonatal modified Kidney Diseases: Improving Global Outcomes AKI criteria and provide the rationale for its use as the standardized definition of neonatal AKI. We discuss risk factors for neonatal AKI and suggest which patient populations may warrant closer surveillance, including neonates <1500 g, infants who experience perinatal asphyxia, near term/ term infants with low Apgar scores, those treated with extracorporeal membrane oxygenation, and those requiring cardiac surgery. We provide recommendations for the evaluation and treatment of these patients, including medications and renal replacement therapies. We discuss the need for long-term follow-up of neonates with AKI to identify those children who will go on to develop chronic kidney disease. This review highlights the deficits in our understanding of neonatal AKI that require further investigation. In an effort to begin to address these needs, the Neonatal Kidney Collaborative was formed in 2014 with the goal of better understanding neonatal AKI, beginning to answer critical questions, and improving outcomes in these vulnerable populations.